LOCALIZATION OF ACCESSORY PATHWAY IN PATIENTS WITH WOLFF-PARKINSON-WHITE SYNDROME FROM SURFACE ECG USING ARRUDA ALGORITHM - Saidullah, Shahab; Shah, Bakhtawar; Ullah, Hameed; Aslam, Zahid; Khan, Muhammad Aleem (Journal of Ayub Medical College Abbottabad, 2016)
Background: To ablate accessory pathway successfully and conveniently, accurate localization of the pathway is needed. Electrophysiologists use different algorithms before taking the patients to the electrophysiology (EP) laboratory to plan the intervention accordingly. In this study, we used Arruda algorithm to locate the accessory pathway. The objective of the study was to determine the accuracy of the Arruda algorithm for locating the pathway on surface ECG. Methods: It was a cross-sectional observational study conducted from January 2014 to January 2016 in the electrophysiology department of Hayat Abad Medical Complex Peshawar Pakistan. A total of fifty nine (n=59) consecutive patients of both genders between age 14-60 years presented with WPW syndrome (Symptomatic tachycardia with delta wave on surface ECG) were included in the study. Patient’s electrocardiogram (ECG) before taking patients to laboratory was analysed on Arruda algorithm. Standard four wires protocol was used for EP study before ablation. Once the findings were confirmed the pathway was ablated as per standard guidelines. Results: A total of fifty nine (n=59) patients between the age 14-60 years were included in the study. Cumulative mean age was 31.5 years±12.5 SD. There were 56.4% (n=31) males with mean age 28.2 years±10.2 SD and 43.6% (n=24) were females with mean age 35.9 years±14.0 SD. Arruda algorithm was found to be accurate in predicting the exact accessory pathway (AP) in 83.6% (n=46) cases. Among all inaccurate predictions (n=9), Arruda inaccurately predicted two third (n=6; 66.7%) pathways towards right side (right posteroseptal, right posterolateral and right antrolateral). Conclusion: Arruda algorithm was found highly accurate in predicting accessory pathway before ablation. Keywords: accessory pathway; Arruda algorithm; electrophysiology; Ablation, electrocardiogram